Risk Factors of Urethro-cutaneous Fistula Development in Hypospadias Surgery - Wien Permana; Tarmono Tarmono; Johan Renaldo (Fakultas Kedokteran Universitas Brawijaya, 2021)
Urethrocutaneous fistula development is the most common complication found hypospadias surgery. Several factors associated with the incidence of fistulas are the age at the time the surgery. The type of hypospadias, the degree of chordae, the operative technique applied and catheter type. This study aimed to determine the risk factors associated with the urethro-cutaneous fistula development in hypospadias surgery. The results showed that from 310 hypospadias patients undergoing urethroplasty, urethra cutaneous fistula development occurred among 105 patients (30.6%) with a mean age of surgery 10.89+6.27 years. Hypospadias type has a significant difference with the incidence of urethro-cutaneous fistula development (p = 0.027). Age (p = 0.615), degree of chordae (P=0.805), operative technique (P=0.901) and catheter type (P=691) do not have a significant impact to urethro-cutaneous fistula development. It can be concluded that operative urethroplasty has a risk of urethra-cutaneous fistula that associated with hypospadias type.